Interval shrinkage estimation of the parameter of exponential distribution in the presence of outliers under loss functions - Parviz Nasiri (Statistics in Transition new series (SiTns), 2022)
In this paper, we studied estimators based on an interval shrinkage with equal weights point shrinkage estimators for all individual target points ¯θ ∈ (θ0,θ1) for exponentially distributed observations in the presence of outliers drawn from a uniform distribution. Estimators obtained from both shrinkage and interval shrinkage were compared, showing that the estimators obtained via the interval shrinkage method perform better. Symmetric and asymmetric loss functions were also used to calculate the estimators. Finally, a numerical study and illustrative examples were provided to describe the results.
Keywords: 519; interval information; mean square error; shrinkage estimator; exponential distribution; uniform distribution; outliers; Linex loss function